Developing a Self-Reflection Tool to Assess Schools’ Openness - Sotiriou, Menelaos; Sotiriou, Sofoklis; Bogner, Franz X. (Frontiers in Education, 2021)
In 2015, the EU Educational Policy document “Science Education for Responsible Citizenship” introduced the concept of Open Schooling as a promising approach to transform schools to innovation hubs within their local communities. In an open school environment, external ideas need to challenge traditional internal views and, in turn, to benefit its students as the community it serves. Such engaging environments may vitally contribute their community when students’ projects introduce real needs into a community outside of school, present them publicly and enrich local expertise. Additionally, such school environments may foster learner independence – and interdependence – through collaboration and through the provision of opportunities for learners to understand and interrogate their place in the world. In our study, that was realised in the framework of the European Union supported Coordination Action called “Open Schools for Open Societies” (OSOS), we have analysed the development process of a large number of schools with a Self-Reflection Tool (OSOS-SRT), focusing on the organisational change during the implementation of the open schooling approach. Rooted in the theory of RRI (Responsible Research and Innovation) principles, the tool has shown its potential to analyse the openness level of each school. In this paper, we are presenting the validation of the proposed instrument and empirical data from the overall transformation process. The school environments were evaluated for one full academic year by completing two measurements, one before their involvement and one after their engagement in the transformation journey. Participating schools achieved an average increase of 11.34% in their openness levels, while based on the first measurement the lowest performers achieved a 35-45% increase while the higher scorer still reached a small but significant increase in the recorded openness levels. Our findings could act as a reference point for educational policy actions to support school development through cooperation and continuous interaction with external stakeholders. Consequences for school management, development plans and teachers’ professional development are discussed.